Design and Development of swarm AGV’s alliance for Search and Rescue operations - Pyla, Ratan; Pandalaneni, Vikranth; Raju, P Jeevan Narayana; G, Guga Priya (Journal of Robotics and Control (JRC), 2023)
Rapid response is essential for saving lives in search and rescue operations since the amount of time is critical. In this project, a swarm of autonomous ground vehicles (AGVs) equipped with ROS-based software architecture will be designed and built for rapid search and rescue missions. The swarm of AGVs will function autonomously to navigate through challenging areas and be outfitted with a variety of sensors, including cameras, and LIDAR. The proposed system will be capable of performing 2D mapping, live video surveillance, autonomous navigation, victim/object detection, and two-way audio communication. The goal of the project is to reduce the risk to human life in dangerous areas by providing a quick and efficient response system for search and rescue operations. A centralized management system with a de-centralized module will be created as part of the project to keep an eye on and manage the AGV horde. However, there will be a functionality to take control of a specific robot in the swarm network when needed. In difficult areas where it might not be safe for humans to operate, the suggested method will enable quick and efficient search and rescue operations.